2018
DOI: 10.15282/jmes.12.4.2018.16.0362
|View full text |Cite
|
Sign up to set email alerts
|

Effect of end chills, reinforcement content and carburization on the hardness of LM25-borosilicate glass particulate composite

Abstract: Aluminium metal matrix composites (AMCs) are widely employed in aerospace and automobile applications. Thus, they are required to operate reliably under a severe corrosive, high temperature and carbonaceous environments, without undergoing any deterioration in their mechanical properties. The paper is the compilation of the experimental results and analysis carried out to investigate the effect of different end chills, reinforcement content and carburization on the LM25 aluminium alloy reinforced with borosili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…These conditions are, on the one hand, promotes the increasing of λ1 and λ2; on the other hand, practically decreases the HV (Figure 5a). The similar result of the influence of the solidification parameters on improving the HV has reported by [7,[22][23][24][25][26]. High HV is at the minimum λ1 and λ2, and it gradually decreases as λ1 and λ2 increases.…”
Section: Microstructure Parameterssupporting
confidence: 82%
“…These conditions are, on the one hand, promotes the increasing of λ1 and λ2; on the other hand, practically decreases the HV (Figure 5a). The similar result of the influence of the solidification parameters on improving the HV has reported by [7,[22][23][24][25][26]. High HV is at the minimum λ1 and λ2, and it gradually decreases as λ1 and λ2 increases.…”
Section: Microstructure Parameterssupporting
confidence: 82%
“…Also AMCs exhibit improved resistance to corrosion and deformation, combined with excellent strength and elastic modulus [14,15]. AMCs reinforced with particles derived from oxides and carbides of ceramic materials such as SiC, Al 2 O 3 , B 4 C, SiO 2 , WC and MgO possess superior mechanical, thermal and electrical properties and were shown to perform better than their monolithic metallic counterparts in severe operating conditions requiring resistance to high temperatures and pressures [16][17][18][19]. Karthikraja et al reported that the inclusion of SiC and Al 2 O 3 particles within an aluminum alloy (Al 7075) matrix resulted in the production of stronger interfaces between the particles and the matrix alloy, which in turn reduced the rate of corrosion [20].…”
Section: Introductionmentioning
confidence: 99%
“…Hiremath investigated LM25-borosilicate glass particle composites using the stir casting method, and the findings show that the hardness improves linearly as the reinforcement amount inside the matrix increases. It is also clear that the cold material's Volumetric Heat Capacities have a significant impact not only on the quality of the castings produced but also on the hardness of the AMCs [24]. Elango et al [11] studied the wear properties of LM25 and composites supplemented with SiC and Titanium Dioxide (TiO2).…”
Section: Introductionmentioning
confidence: 99%